When encryption fails: a glimpse behind the curtain of synthetic drug trafficking networks - Soudijn, Melvin R. J. (The criminology of Carlo Morselli ; part 2, 2024)
The confiscation of the server of an encrypted telephone provider resulted in the retrieval of millions of text messages about covert activities that were overtly discussed between criminals. It provided a unique window into serious organised crime and the people involved. In this article, a social network analysis was carried out on accounts who communicated about synthetic drug trafficking. The sheer number of accounts (N = 4,158) and messages threads (12,085) allows for a meso level analysis of the structural characteristics of the networks involved. Three findings stand out. Firstly, the majority (58%) of the accounts active in the synthetic drug market is involved in poly-drug trafficking. Secondly, three-quarters of all accounts are interconnected in a giant component, resulting in a criminal small-world effect. Thirdly, the network appears to be robust. As a consequence, the removal of central accounts will hardly have any impact on the network as a whole.